Evaluation of vascular aging on measures of cardiac function and mechanical efficiency: insights from in-silico modeling - Mulligan, Lawrence J.; Thrash, Julian; Mitrev, Ludmil; Folk, Douglas; Exarchakis, Alyssa; Ewert, Daniel; Hill, Jeffrey C. (Frontiers in Cardiovascular Medicine, 2024)
Introduction This study evaluated the hypothesis that vascular aging (VA) reduces ventricular contractile function and mechanical efficiency (ME) using the left ventricular pressure-volume (PV) construct. Methods A previously published in-silico computational model (CM) was modified to evaluate the hypothesis in two phases. In phase I, the CM included five settings of aortic compliance (CA) from normal to stiff, studied at a heart rate of 80 bpm, and phase II included the normal to stiff CA settings evaluated at 60, 100, and 140 bpm. The PV construct provided steady-state and transient data through a simulated vena caval occlusion (VCO). The steady-state data included left ventricular volumes (EDV and ESV), stroke work (SW), and VCO provided the PV area (PVA) data in addition to the three measures of contractile state (CS): end-systolic pressure-volume relationship (ESPVR), dP/dtmax-EDV and preload recruitable stroke work (PRSW). Finally, ME was calculated with the SW/PVA parameter. Results In phase I, EDV and ESV increased, as did SW and PVA. The impact on the CS parameters demonstrated a small decrease in ESPVR, no change in dP/dtmax-EDV, and a large increase in PRSW. ME decreased from 71.5 to 60.8%, respectively. In phase II, at the normal and stiff CA settings, across the heart rates studied, EDV and ESV decreased, ESPVR and dP/dtmax-EDV increased and PRSW decreased. ME decreased from 76.4 to 62.6% at the normal CA and 65.8 to 53.2% at the stiff CA. Discussion The CM generated new insights regarding how the VA process impacts the contractile state of the myocardium and ME.